Genetic markers identify duplicates in Nordic potato collections - Chrominski, Pawel; Carlson-Nilsson, Ulrika; Palmé, Anna; Kirk, Hanne Grethe; Asdal, Åsmund; Ansebo, Lena (Frontiers in Plant Science, 2024)
The first small scale cultivation of potatoes in the Nordic countries began roughly 300 years ago, and later became an important staple food in the region. Organized conservation efforts began in the 1980s, and today, potato landraces, improved varieties, and breeding lines are conserved in genebanks at the Nordic Genetic Resource Center (NordGen), Sweden, and the Norwegian Genetic Resource Centre (NGS), Norway, as well as at potato breeding companies across Nordic countries. All these collections house a diverse array of genotypes with local names and local growing histories from the whole region. However, the presence of duplicates, and inconsistent naming has led to confusion. In this study, 198 accessions of cultivated potato (Solanum tuberosum L.) have been genotyped with 62 microsatellite (SSR) markers. The analyzed accessions came from three collections: 43 accessions from the Danish Potato Breeding Foundation in Vandel (LKF-Vandel), 90 from NordGen and 65 from NGS. The genetic analysis revealed 140 unique potato genotypes and 31 groups/clusters of duplicates, most of which contained duplicate pairs and the others three to ten accessions. Several accessions with distinct names were genetically identical or very similar, suggesting historical sharing, and regional distribution of seed potatoes, leading to the emergence of diverse local names. Moreover, many improved varieties from early potato breeding were revealed to have duplicates that have been considered Nordic landraces. Furthermore, potato accessions with identical names but originating from different collections were confirmed to be duplicates. These findings have already influenced management decisions and will further improve management practices for Nordic potato collections. Additionally, this new knowledge will benefit Nordic potato breeding efforts and allow for the dissemination of more accurate information to other users of potato diversity.